Kepemimpinan Pribadi dan Sosial (Leadership) dalam Perspektif Hadis - Ibnu, Ibnu (Analisis: Jurnal Studi Keislaman, 2017)
The main task of humans as the Caliph on earth, cause consequences for human beings able to account for every action in life. At least, man must be a "leader" for himself, and in a social community,he can be a leader too. Through thematic studies, using the term ra'in, khalifa, amir, and imam, it is found that there are at least 5 criteria of good leaders according to the Prophet, that is has a good leadership, professional, has the ability to perform tasks well, adjust to aspirations of the community, and musyawarah.